Nailfold capillaries in connective tissue diseases in skin of color: A dermoscopic view - Balachandra S Ankad; Priyanka S Jaju (Wolters Kluwer Medknow Publications, 2019)
Introduction: Dermoscopy has gained tremendous importance in the recent past. It helps in the visualization of subsurface structures, whereby details of skin lesion are studied in depth. Nailfold capillaries are involved early in the course of disease process in connective tissue diseases. Videocapillaroscopy is used to examine the patterns in the nailfold capillaries. However, training, cost, and skilled technique limits the use of it. Dermoscopy, being handheld and easy to perform, is best alternative to videocapillaroscopy. Authors evaluated the utility of dermoscopy in the study of nailfold capillaries in connective tissue diseases in patient with the skin of color. To the best knowledge of authors, this is the first study from the Indian subcontinent. Materials and Methods: The study was conducted in a tertiary care hospital from January 2017 to June 2017. It was a cross-sectional pilot study. Sixteen consecutive patients with connective tissue diseases were included in the study. Connective tissue diseases comprised of systemic sclerosis, lupus erythematosus, mixed connective tissue disease, dermatomyositis, and rheumatoid arthritis. DermLite 3 dermoscope with Sony camera was employed. Polarized mode and ultrasound gel were used. Results: Of 16 patients, three, two, and three had systemic sclerosis, systemic lupus erythematosus, and discoid lupus erythematosus, respectively. Mixed connective tissue disease, dermatomyositis, and rheumatoid arthritis were seen in one, one, and five patients, respectively. One patient had Rowell syndrome. Scleroderma and nonspecific scleroderma patterns were observed in 75% and 12.5% of patients, respectively. In two patients, the nailfold capillaries appeared normal. Conclusion: Dermoscopy is an in vivo cost-effective method for studying nailfold capillaries in connective tissue diseases. Results obtained using handheld dermoscope were comparable to that of a videocapillaroscope. Authors recommend further studies involving large sample size of the population with skin of color to affirm the nailfold capillaries pattern observed in this study.